PERENCANAAN SUMBER DAYA MANUSIA PENDIDIKAN (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
Human Resources is a major component and as a determinant of success and failure in an organization or educational institution. Educational institutions really need competent human resources in order to support the success and achievement of goals. Human resources are the drivers of a system and all facilities, assets, curriculum, facilities, infrastructure and all other resources. All educational resources cannot function optimally if they are not supported by the availability of human resources. Educational institutions need to carry out a strategic, integrated, interrelated, and comprehensive human resources education planning through the management of education human resources in determining the desired movements of educators and education personnel in the future. The existence of human resource planning Education, then can provide direction for educational institutions as a whole about the human resources needed, human resource activities to be managed and developed, can improve the effectiveness and efficiency of the institution as well as for educators and education staff, so that it can be integrated with short-term planning goals and long-term educational institutions.